2014
DOI: 10.1111/echo.12584
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Vortices as Observed by Vector Flow Mapping: Main Determinants and their Relation to Left Ventricular Filling

Abstract: Vector flow mapping allowed visualization and measurement of several parameters defining vortex behavior inside the cardiac cycle. The differences observed in these parameters between vortices in different phases of the cardiac cycle may be related to their role in optimizing cardiac function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 21 publications
5
26
0
Order By: Relevance
“…In our analysis, although the weak counterclockwise vortex quickly diminished, the strong clockwise vortex continued until the isovolumic contraction phase, as reported previously [2, 5, 2023]. The vortex enables efficient blood streaming and minimizes the flow dissipative EL [2427].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In our analysis, although the weak counterclockwise vortex quickly diminished, the strong clockwise vortex continued until the isovolumic contraction phase, as reported previously [2, 5, 2023]. The vortex enables efficient blood streaming and minimizes the flow dissipative EL [2427].…”
Section: Discussionsupporting
confidence: 82%
“…Blood flow in a healthy human left ventricle forms an energetically efficient vortex [1, 2]. This vortex facilitates inflow into the ventricle, minimizes the dissipation of energy, preserves momentum, and redirects the flow toward the left ventricular outflow [37].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the independent predictors of vorticity other than LV length was peak E wave velocity. Both the vortex and transmitral flow are considered to be influenced by ventricular relaxation 5 , and it is not surprising that the strength of the vortex correlates with the peak E wave velocity in the present study as also reported in study in humans 16 . On the other hand, the relationship between vorticity and peak E can change depending on the pathological conditions.…”
Section: Discussionsupporting
confidence: 87%
“…On the other hand, the relationship between vorticity and peak E can change depending on the pathological conditions. When a relaxation abnormality is observed, the vortex is strongly correlated with the E wave 16 . However, in the volume overloading model dogs, despite the inflow velocity was higher, the obtained vortex strength was weaker than in the normal dog 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Conventionally, only data received in the direction of the beam are extracted from the Doppler information. Vector Flow Mapping (VFM) is an innovative approach that uses color Doppler velocity data, sound fluid dynamic assumptions, and mathematical techniques to derive intracardiac blood flow distributions in an observation plane, and generates 2D images of the corresponding evolving velocity fields [2729]. VFM is often able to sketch out the principal structures of intraventricular flows.…”
Section: Digital Noninvasive Imaging Of Intraventricular Diastolicmentioning
confidence: 99%